Efikasi Bakterisidal Klorheksidin terhadap Escherichia coli dan Klebsiella pneumoniae Penghasil ESBL - Ariningpraja, Rustiana Tasya; Lestari, Retno; Susanto, Akhiyan Hadi; Salam, Mohammad Nurus; Asih, Setya; Febriano, Luis Figo (ARTERI : Jurnal Ilmu Kesehatan, 2025)
Nosocomial infections caused by multidrug-resistant bacteria, such as Escherichia coli and Klebsiella pneumoniae producing Extended-Spectrum Beta-Lactamases (ESBL), present a major challenge in healthcare. These bacteria reduce the effectiveness of antibiotics, worsening patient conditions. This study aims to evaluate the effectiveness of chlorhexidine in disinfecting medical devices contaminated with ESBL-producing bacteria. The methodology involves inoculating bacterial strains on plastic medical device surfaces and disinfecting them with chlorhexidine concentrations of 2.5%, 5%, and 7.5% for 10 minutes, with control groups using sterile water and 70% alcohol. The results indicate that chlorhexidine inhibited the colonies of E. coli and K. pneumoniae effectively, with the highest inhibition occurring at 7.5% for E. coli and at 2.5% for K. pneumoniae. This indicates that these bacteria respond differently to higher levels of chlorhexidine. Through cell lysis and membrane disruption, chlorhexidine shows vast promise as a disinfectant for medical devices against healthcare-associated infections.